(untitled) (Journal of Asian Development Studies, 2025)
This paper investigates the phenomenon of women politicians’ social capital. It also focuses on the strategies women use to navigate the challenges of a political career. The research was qualitative, and the data were collected through random sampling. An unstructured interview guide was used for data Collection. 30 women politicians from various political parties were interviewed to gain in-depth insight into the phenomenon. The results exposed that women face many challenges like restrictions in political mobility, patriarchal system, gender discrimination and harassment in their political career. However, they use some strategies to overcome these barriers.